IMPLEMENTASI PENDIDIKAN AKHLAQ DI SMP MUHAMMADIYAH 9 SURABAYA SEBAGAI SEKOLAH AKHLAQ - Moh. Rifqi Abdillah (Hijri, 2025)
Education plays a crucial role in transforming individuals with negative behavior into those with good character, and one of the most important forms of education in this era is moral education. Moral education is not only relevant in addressing the challenges of globalization but also serves as a solution for developing strong personalities amidst the pervasive influence of foreign cultures and other negative aspects. This study aims to examine how moral education is implemented at SMP Muhammadiyah 9 Surabaya, a character-based school with the motto “Achievement with Morality.” The research adopts a qualitative ethnographic approach grounded in the naturalistic or phenomenological paradigm, utilizing observation, interviews, and documentation as data collection techniques. In shaping students' morals, the roles of teachers and parents are essential, particularly in monitoring all student activities. SMP Muhammadiyah 9 Surabaya offers various programs designed to build students' moral character, such as the Nine Superior Programs, extracurricular activities, and daily habituation practices at school."